2016
DOI: 10.1111/os.12284
|View full text |Cite
|
Sign up to set email alerts
|

What Role Does Low Bone Mineral Density Play in the “Killer Turn” Effect after Transtibial Posterior Cruciate Ligament Reconstruction?

Abstract: The low BMD group demonstrated an inferior biomechanical outcome to the control group with the transtibial technique. With low BMD, the "killer turn" effect compromises the posterior tibial cortex by enlarging the tunnel inlet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Arthroscopic PCL reconstruction is a challenging procedure compared with ACL reconstruction because of the limited visualization, the proximity of the neurovascular structures, the difficulty in passing the graft, and the killer turn effect. 4 , 5 , 23 In a biomechanical study, Bergfeld et al 2 reported that the grafts in the transtibial groups showed significant thinning and fraying at the site of the killer turn. To reduce or avoid the effect of the killer turn, surgeons have adopted improved techniques, such as the tibial inlay technique 33 and modified tibial tunnel techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopic PCL reconstruction is a challenging procedure compared with ACL reconstruction because of the limited visualization, the proximity of the neurovascular structures, the difficulty in passing the graft, and the killer turn effect. 4 , 5 , 23 In a biomechanical study, Bergfeld et al 2 reported that the grafts in the transtibial groups showed significant thinning and fraying at the site of the killer turn. To reduce or avoid the effect of the killer turn, surgeons have adopted improved techniques, such as the tibial inlay technique 33 and modified tibial tunnel techniques.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, this method is also commonly applied worldwide. 15 The patient’s condition is evaluated prior to the use of allogeneic tendons, and all patients are required to provide written informed consent. Although serious complications such as joint infection and graft rejection are possible, no such complications were observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 28 Moreover, between the PCL graft and tunnel wall at the tunnel aperture, it is likely that high mechanical stress occurs on both the femoral side (the critical bending angle) 15 , 23 and the tibial side (killer turn). 26 , 27 , 29 These mechanical factors may facilitate larger graft elongation, tunnel enlargement, and consequently greater postoperative increases in the PTT in the early postoperative term. Meanwhile, no progressive incremental increase in the PTT was observed from 3 months to up to 4.5 years after PCLR in the current study.…”
Section: Discussionmentioning
confidence: 99%